Evaluation of metabolism dependent inhibition of CYP2B6 mediated bupropion hydroxylation in human liver microsomes by monoamine oxidase inhibitors and prediction of potential as perpetrators of drug interaction. (25th March 2015) - Nirogi, Ramakrishna; Palacharla, Raghava Choudary; Mohammed, Abdul Rasheed; Manoharan, Arunkumar; Ponnamaneni, Ranjith kumar; Bhyrapuneni, Gopinadh
Highlights: Clorgyline, pargyline, phenelzine, selegiline are MDI's of CYP2B6. Clorgyline, pargyline, phenelzine, selegiline formed GSH adducts with CYP2B6 enzyme. Likelihood of drug interaction between selegiline and CYP2B6 substrates is remote. Caution is required when phenelzine is co-administered with CYP2B6 substrates. Abstract: The objective of the study was to evaluate the metabolism dependent inhibition of CYP2B6 catalyzed bupropion hydroxylation in human liver microsomes by monoamine oxidase (MAO) inhibitors and to predict the drug–drug interaction potential of monoamine oxidase inhibitors as perpetrators of drug interaction. Human liver microsomal CYP2B6 activities were investigated using bupropion hydroxylation as probe substrate marker. The results from single point time dependent inhibition and shift assays suggest that clorgyline, pargyline, phenelzine, and selegiline were metabolism based inhibitors of CYP2B6. In IC50 shift assays, clorgyline, pargyline, phenelzine and selegiline are metabolism based inhibitors of CYP2B6 with fold shit of 3.0-, 3.7-, 2.9-, and 11.4-fold respectively. The inactivation of clorgyline was characterized by K I value of 2.5 ± 0.3 and k inact value of 0.045 ± 0.001 min −1 . Phenelzine inactivated CYP2B6 with K I and k inact values of 44.9 ± 6.9 μM and 0.085 ± 0.003 min −1 respectively. Inactivation of selegiline was characterized with K I and k inact values of 22.0 ± 3.3 and 0.074 ± 0.002 min −1 respectively. The inactivation caused by these inhibitors was not reversed by dialysis indicating irreversible inhibition. Based on the mechanistic static model, selegiline showed an increase in the area under the curve (AUC) of efavirenz and bupropion by 1.01-fold. Phenelzine predicted to cause an increase in the AUC of efavirenz and bupropion by 9.4- and 2.4-fold respectively considering unbound hepatic inlet concentrations of phenelzine. In conclusion, the results from this study demonstrated that MAO inhibitors can inactivate human liver microsomal CYP2B6. The likelihood of drug interaction when selegiline co-administered with CYP2B6 substrates is remote. Caution is required while co-administering phenelzine with substrates that are exclusively metabolized by CYP2B6 enzyme and substrates that have narrow therapeutic index.